2021
DOI: 10.1186/s12872-021-02417-4
|View full text |Cite
|
Sign up to set email alerts
|

Spectrum of cardiovascular diseases at a referral tertiary care hospital in Somalia, Mogadishu: an echocardiographic study

Abstract: Background To investigate the frequencies and patterns of cardiovascular diseases (CVDs), including rheumatic and congenital heart diseases, among patients with abnormal hearts assessed by echocardiographic examination. Methods This retrospective, descriptive registry reviewed abnormal echocardiographic findings of 1140 patients aged 0–100 years who were admitted to the cardiology outpatient clinic at a tertiary training institution in Mogadishu. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 31 publications
0
2
0
Order By: Relevance
“… 19 An echocardiographic study done in referral hospitals of Mogadishu also reported that the prevalence of VHD was 34.6% which is in line with the current findings. 20 Another community-based cross-sectional study conducted in Dar es Salaam, Tanzania, reported the prevalence of rheumatic heart disease was 34 per 1000 among school children. 21 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“… 19 An echocardiographic study done in referral hospitals of Mogadishu also reported that the prevalence of VHD was 34.6% which is in line with the current findings. 20 Another community-based cross-sectional study conducted in Dar es Salaam, Tanzania, reported the prevalence of rheumatic heart disease was 34 per 1000 among school children. 21 …”
Section: Discussionmentioning
confidence: 99%
“…19 An echocardiographic study done in referral hospitals of Mogadishu also reported that the prevalence of VHD was 34.6% which is in line with the current findings. 20 Another community-based cross-sectional study conducted in Dar es Salaam, Tanzania, reported the prevalence of rheumatic heart disease was 34 per 1000 among school children. 21 According to the current study, VHD patterns of VHD were identified and multiple VHDs involving two or more valves were the most commonly diagnosed VHD which was 49.5%.…”
mentioning
confidence: 99%